Teratoma cervical congênito gigante: relato de caso e revisão quanto às opções terapêuticas - Miele, Camila Ferro [UNIFESP] (2011)
OBJECTIVE: To report a case of congenital cervical teratoma, highlighting the severity and the therapeutic difficulties associated. CASE DESCRIPTION: A 30-year old mother, with pregnancy by assisted fertilization. At 23 weeks, a cervical fetal malformation was diagnosed. A cesarean section was indicated with 31 weeks due to fetal distress. A male newborn infant with birth weight of 1800g and Apgar score of 4/9 presented a large right cervical tumor, with extensions to the mandible and to the upper chest. Patient presented congestive heart failure due to flow steal by the tumor 40 hours after birth, which caused progressive respiratory, hemodynamic and renal deterioration refractory to vasopressors, volume replacement and increased ventilatory support. Tumor resection was indicated, but the clinical instability of the patient did not allow his transport to the operating room and the infant died 70 hours after birth. COMMENTS: The case is representative of the difficulties related to postnatal treatment of bulky cervical teratomas. Despite prenatal diagnosis, the patient developed airway obstruction, complicated by refractory cardiogenic shock. The surgical approach during delivery is crucial for survival. Nowadays, management includes surgical removal of the tumor while maintaining the maternal-fetal circulation, allowing continuous fetal oxygenation. The clinical course described in the case is consistent with the literature that reports poor prognosis when the intra-partum surgical approach is not performed.